Grit and motivation as predictors of stages of change towards weight control in an adult population - Marentes-Castillo, María; Castillo, Isabel; Tomás, Inés; Zamarripa, Jorge; Álvarez, Octavio (Anales de Psicología / Annals of Psychology, 2022)
Given the increasing percentage of overweight and obesity worldwide, weight control is a primary health-promoting behaviour. Integrating Grit personality, self-determination theory, and the transtheoretical model of change, this study evaluates Grit personality and motivation as psychological antecedents of the stages of change towards weight control. A total of 1351 Mexican adults between 18 and 65 years of age completed a packet of questionnaires on the variables of interest. The results showed that Grit personality was positively and significantly related to the maintenance, action, preparation, and contemplation stages, and negatively and significantly related to the precontemplation stage, through the types of motivation (autonomous, controlled, and amotivation), suggesting that Grit personality and motivation are important attributes to take into account in the change towards weight control. This study provides tools to help professionals involved in nutritional consultation to understand weight control adherence, thus promoting a better interdisciplinary approach to overweight and obesity.